2007
DOI: 10.1038/ng2135
|View full text |Cite
|
Sign up to set email alerts
|

The role of site accessibility in microRNA target recognition

Abstract: MicroRNAs are key regulators of gene expression, but the precise mechanisms underlying their interaction with their mRNA targets are still poorly understood. Here, we systematically investigate the role of target-site accessibility, as determined by base-pairing interactions within the mRNA, in microRNA target recognition. We experimentally show that mutations diminishing target accessibility substantially reduce microRNA-mediated translational repression, with effects comparable to those of mutations that dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
2,066
1
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 2,223 publications
(2,108 citation statements)
references
References 30 publications
30
2,066
1
11
Order By: Relevance
“…Both the 3′UTRs, 5′UTRs and CDS regions were used to predict targets by two widely used miRNA target prediction algorithms, miRanda (http://www.microrna.org/microrna/home.do) and PITA (Kertesz et al, 2007) (http://genie.weizmann.ac.il/pubs/ mir07/mir07_exe.html). The criteria of miRanda for potential target sites were as follows: 1) S, the sum of single-residue-pair match scores over the alignment, ≥ 140 and 2) ΔG, the free energy of duplex formation, b − 17 kcal/mol.…”
Section: Prediction Of Mirna Target Genes Via Computational Analysismentioning
confidence: 99%
“…Both the 3′UTRs, 5′UTRs and CDS regions were used to predict targets by two widely used miRNA target prediction algorithms, miRanda (http://www.microrna.org/microrna/home.do) and PITA (Kertesz et al, 2007) (http://genie.weizmann.ac.il/pubs/ mir07/mir07_exe.html). The criteria of miRanda for potential target sites were as follows: 1) S, the sum of single-residue-pair match scores over the alignment, ≥ 140 and 2) ΔG, the free energy of duplex formation, b − 17 kcal/mol.…”
Section: Prediction Of Mirna Target Genes Via Computational Analysismentioning
confidence: 99%
“…Of these, 1103 were downregulated and 758 upregulated. By using the Probability of Interaction by Target Accessibility (PITA) algorithm (Kertesz et al, 2007), we identified predicted miR-21 targets in the list of differentially expressed genes, and calculated the distribution and cumulative distribution functions of the predicted targets and the nontarget probe sets (Grimson et al, 2007) (Figure 7a). The two distributions belong to different populations with a P-value o1*10 À5 according to the two-sample Kolmogorov-Smirnov test, confirming that the overexpression of mir-21 downregulates preferentially its predicted targets, among which we found some of the known miR-21 targets (Btg2, Fam3c, Hipk3, Itgb1 and Pdcd4).…”
Section: Regulation Of Mir-21 By Ras and Its Role In Cancer D Frezzetmentioning
confidence: 99%
“…Cyclin B1 is known to be expressed predominantly in the G2/M phase of cell division (Pines and Hunter, 1989). Finally the hub UBE2 complex contains both downregulated genes and predicted mir-21 targets according to the PITA algorithm (John et al, 2004;Kertesz et al, 2007).…”
Section: Regulation Of Mir-21 By Ras and Its Role In Cancer D Frezzetmentioning
confidence: 99%
“…Since target RNA accessibility is of importance for miRNA target recognition [48] and siRNA functioning [49], we hypothesized that the increased inhibitory potential of the GGAA-bulge TuD as compared to the GTCA-bulge TuD may have been caused by an altered and more relaxed secondary TuD structure. A relaxed secondary TuD structure may increase the RNA accessibility compared to a less open structure, which may lead to an increased capacity for scavenging mature miRNA targets.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we observed that the 4 nt bulge sequence is an important contributor to the opening energy of the TuD hairpin structure and that the calculated TuD opening energy inversely correlated with its efficiency (Figure 2(a-c)). Since accessibility of miRNA target sites is important in miRNA functioning [48], it suggests that a low opening energy induces a more relaxed TuD structure, which may enable enhanced MBS exposure and more efficient miRNAs scavenging. This is in line with a report on synthetic TuDs, in which the authors showed that strong base pairing between two fully 2′ -O- methylated RNA strands impaired the inhibitory potential.…”
Section: Discussionmentioning
confidence: 99%